Report of intravitreal injection of Ranibizumab for macular edema caused by central retinal vein occlusion - Jing-Yi Lai (Guoji Yanke Zazhi, 2016)
AIM:To investigate the clinical effect of intravitreal injection of Ranibizumab for macular edema caused by central retinal vein occlusion(CRVO). METHODS: Selected 30 patients(30 eyes)from March～September 2015 in our hospital with CRVO complicated by macular edema were treated with intravitreal injection of ranibizumab, 1 time per month, 1～3mo as one course. After treatments, all patients were followed up for 3mo. The best corrected visual acuity(BCVA), intraocular pressure(IOP), central macular thickness and macular edema regressive rate and fundus fluorescein angiography were compared and analyzed. RESULTS:With the increase of injection times of ranibizumab, BCVA in patients had a gradual increase(P<0.05). Central macular thickness significantly decreased(P<0.05), and IOP had no significant change(P>0.05). After the 1st, 2nd and 3th injection, the macular edema regressive rates were 47%, 68%, 94%. CONCLUSION:Intravitreal injection of ranibizumab can significantly relieve the macular edema caused by CRVO and improve BCVA of the patients.